The Mediation Role of Brand Trust on Repurchase Intention: The Influence of Brand Image and Celebrity Endorsers: Case Study of Customer Noera Collagen Drink on the TikTok Shop Application in Malang - Ghasela Azizah; Faisol Faisol (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
This research investigates the influence of brand image and celebrity endorsers on repurchase intention, highlighting brand trust as a mediating variable. Conducted among consumers of Noera Collagen Drink on the Malang City TikTok Shop platform, the study employs a descriptive quantitative research approach. The target market consists of consumers who have previously purchased Noera Collagen Drink through the TikTok Shop application and reside in Malang City. A purposive sampling method selected a sample of 100 respondents, with data collected through an online questionnaire via Google Forms. The analysis was performed using SEM PLS in SmartPLS. The findings reveal several significant positive relationships: brand image significantly boosts repurchase intention, celebrity endorsers effectively enhance repurchase intention, and both brand image and celebrity endorsers positively influence brand trust. Furthermore, brand trust is shown to significantly elevate repurchase intention, while brand image and celebrity endorsers affect repurchase intention through the mediation of brand trust. The implications of these findings are crucial for marketing strategies. Organizations should prioritize enhancing their brand image through consistent quality, effective messaging, and emotional connection with consumers. Moreover, selecting the right celebrity endorsers who resonate with the target audience can strengthen brand trust and drive repurchase intentions. The strategic alignment between brand image, celebrity endorsement, and brand trust can lead to increased customer loyalty and repeat business. Additionally, the study underscores the importance of building strong trust relationships with consumers, which can be achieved through transparent communication and engagement. By focusing on these aspects, companies can cultivate a loyal customer base, ultimately enhancing their competitive advantage in the market. Employing these insights can lead to more effective marketing strategies, ensuring that organizations not only attract new customers but also retain existing ones through increased repurchase intentions.